Analisis Profitabilitas Lpd Desa Adat Penglatan Melalui Cash Turn Over, Credit Turn Over Dan Receivable Turn Over - Ni Luh Sri Kasih; I Ketut Suardika (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
The purpose of this study was to determine the total cash turnover ratio (Cash Turn Over), to determine the total credit turnover ratio (Credit Turn Over) and to determine the total receivable turnover ratio (Receivable Turn Over) at the Penglatan Traditional Village Credit Institution. This study uses a quantitative approach. The data collection technique used in this research is documentation. The data analysis technique used in this research is descriptive quantitative method. The location of this research was carried out in the LPD of the Penglatan Traditional Village. The data needed in this study is secondary data, namely the financial statements of the Penglatan Traditional Village LPD for the Year 2019-2021. The data were analyzed using descriptive quantitative analysis techniques. The results show that based on the calculation of the Cash Turn Over Ratio, Credit Turn Over Ratio and Receivable Turn Over Ratio are still below the standard, which means that the Penglatan Traditional Village LPD has not been able to maximize the use of capital. Meanwhile, the Profitability Ratio calculation based on the calculation results shows a fairly high result, which means that the Penglatan Traditional Village LPD can maximize the use of capital.